Clinical outcomes in patients with paracetamol ingestion treated with a two-bag n-acetylcysteine regimen in the emergency centre of khayelitsha hospital - Mbanga, Kedibone (Division of General Surgery, 2024)
Introduction: Paracetamol is frequently ingested for intentional self-poisoning. N-acetylcysteine (NAC) is administered to patients at risk of developing hepatotoxicity and was historically administered using a three-bag intravenous regimen. A change towards a two-bag NAC regimen was initiated at Khayelitsha Hospital. The aim of the study was to describe the clinical outcomes in patients with a history of paracetamol ingestion who were treated with the two-bag NAC regimen. A descriptive comparison to a historical cohort of patients treated with the three-bag NAC regimen was also made. Methods: A retrospective chart review was conducted to assess a 6-month clinical audit. Summary statistics were used to describe all variables. Results: Overall, 57 patients were included (mean age 26 years, 83% female). The median ingested dose (10 g) was similar between the regimens. An empiric indication occurred more in patients receiving the two-bag regimen (84.0% versus 50.0%). The median paracetamol level (231 umol/L) and the proportion of confirmed paracetamol toxicity (32%) were less in the two-bag regimen. A delay in initiating the first NAC infusion occurred in 22 (38.6%) patients. Forty adverse effects were recorded in 22 (38.6%) patients and a higher proportion occurred in the two-bag regime (44.0% vs. 34.4%). Nausea and vomiting occurred frequently (n=30, 52.7%), which were comparable for both regimens. The prevalence of hepatotoxicity after receiving NAC was 8.8% (n=5). Conclusion: A large number of patients were empirically started on NAC with a higher incidence of adverse reactions in the two-bag NAC than in the three-bag NAC regimen in contrast to existing evidence. However, there was a reduction in treatment delay in the two-bag NAC regimen compared to the three-bag NAC regimen.